Development of STEM-Based Teaching Supplements Assisted by Gram Staining Practicum to Optimize Students' Critical Thinking and Science Process Skills - Yuliyani, Rahma; Iswari, Retno Sri; Anggraito, Yustinus Ulung (Journal of Innovative Science Education, 2023)
Changes in the learning paradigm in higher education develop along the times. In the 21 st century, one of the roles of higher education institutions is to act as a liaison with changes in the job market. Minister of Education and Culture No. 3 in the year 2020 states that the two of several characteristics of the learning process in the KKNI curriculum are integrative and scientific. The teaching supplements were developed as an effort to fulfill the integrative and scientific characteristics. This research examines the validity and practicality of the developed teaching supplements and looks toward the effect on students' critical thinking skills and science process skills. This research was conducted using the research and development method and the model used was the ADDIE model. The developed teaching supplement has very valid and very practical criteria so that it can be applied to research samples with minor revisions. Then, the developed teaching supplements are proven to be able to optimize students' critical thinking skills and science process skills. In addition, this research also reveals that critical thinking skills are correlated with science process skills.